Contact improvisation : an introduction to a vitalizing dance form - Pallant, Cheryl (Jefferson, N.C. : McFarland, 2006)
"In this book the author draws upon her own experience and research to explain the art of contact improvisation, in which dance partners propel movement by physical contact. The text begins with a history, then describes the elements that define this form of dance"--Provided by publisher.
Prologue -- The creative body : source of a new form -- The practicing body : contact improvisation fundamentals -- The knowing body : self and identity -- The entitled body : politics and privilege -- The relating body : alienation and orientation -- The tribal body : creating community -- The dancing body : a teacher's sampler.
boek
Keywords: Improvisation in dance -- History